Estudio DISEHTAC II: diagnóstico y seguimiento de la hipertensión arterial en Cataluña. Comparación con los datos de 1996 - Benítez Camps, M. (Aten Primaria, 2005)
OBJECTIVE: To evaluate the changes in the diagnosis and follow-up of hypertension, and in the evaluation of cardiovascular risk, in a population served by primary care centers in Catalonia (northeastern Spain). Management was evaluated with indicators published in the Guidelines for Hypertension for Primary Care (Guía de Hipertensión Arterial para la Atención Primaria). DESIGN: Multicenter, observational, before-after design (1996-2001). SETTING: Primary care. PARTICIPANTS: Twelve primary care centers chosen from among the 31 centers that took part in the DISEHTAC I study (1996), with a total of 990 patient records. MAIN MEASURES: We analyzed age, sex, date of diagnosis of hypertension, number of blood pressure measurements needed for diagnosis, use of the mean value of duplicate blood pressure determinations, values for all blood pressure measurements in 2001, blood pressure determinations during the preceding 6 months, screening for and diagnosis of diabetes, dyslipidemia, smoking, obesity, and left ventricular hypertrophy. RESULTS: Of the 171 new cases of hypertension, 16.7% were diagnosed from at least 3 duplicate blood pressure measurements or as a result of acute episodes of hypertension. About one third (32.4%) of the patients with hypertension had blood pressure values below 140 and 90 mm Hg (25.7% in 1996), and the difference between the 2 sets of survey results was statistically significant. In three fourths (75.4%) of the patients, blood pressure had been measured during the preceding 6 months; this percentage was not significantly different in comparison to the figure found in 1996. Screening to detect cardiovascular risk factors was done in 50.4% of the patients (63.1% in 1996). CONCLUSIONS: Follow-up for hypertension in Catalonia has improved notably since 1996, but there was no improvement in the diagnosis of risk factors or in the integral evaluation of cardiovascular risk.